2020
DOI: 10.1098/rsta.2020.0045
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic field generation from composition gradients in inertial confinement fusion fuel

Abstract: Experimental asymmetries in fusion implosions can lead to magnetic field generation in the hot plasma core. For typical parameters, previous studies found that the magnetization Hall parameter, given by the product of the electron gyro-frequency and Coulomb collision time, can exceed one. This will affect the hydrodynamics through inhibition and deflection of the electron heat flux. The magnetic field source is the collisionless Biermann term, which arises from the Debye shielding potential in electron pressur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…This form is in agreement with the numerical fit to the Fokker-Planck simulations in reference 14 . On substitution of equation ( 2) into the Maxwell equation ∂ t B = −∇ × E, using ∇.B = 0 and p e = n e eT e , this results in the ExMHD induction equation 21,22…”
Section: Additional Magnetic Source Termmentioning
confidence: 99%
“…This form is in agreement with the numerical fit to the Fokker-Planck simulations in reference 14 . On substitution of equation ( 2) into the Maxwell equation ∂ t B = −∇ × E, using ∇.B = 0 and p e = n e eT e , this results in the ExMHD induction equation 21,22…”
Section: Additional Magnetic Source Termmentioning
confidence: 99%
“…∇ × (∇P e /en e ) is the Biermann battery term and is the dominant source of magnetic flux in the simulations. ∇×β ∇T e /e represents magnetic flux generated by ionization gradients in the plasma [45]. Previous Gorgon simulations of foils did not include this term [37], although it is found here to be of only secondary importance.…”
Section: B Extended-magnetohydrodynamics Simulationsmentioning
confidence: 78%
“…Although there are many subtle effects arising from plasma composition gradients 28,29 , magnetic instabilities have barely been explored, since the Z dependence of β ⊥ is often neglected. Further study 20,30 has found that in low Z plasma regions with steep gradients in Z, this thermal force source term is actually of similar magnitude to the Biermann battery source term. This was previously verified via a kinetic simulation 30 .…”
Section: Extended Mhd Modelmentioning
confidence: 90%